2017
DOI: 10.1103/physreve.95.063208
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of electron-atom collisions to the plasma conductivity of noble gases

Abstract: We present an approach which allows the consistent treatment of bound states in the context of the dc conductivity in dense partially ionized noble gas plasmas. Besides electron-ion and electronelectron collisions, further collision mechanisms owing to neutral constituents are taken into account. Especially at low temperatures T ≈ 1eV, electron-atom collisions give a substantial contribution to the relevant correlation functions. We suggest an optical potential for the description of the electronatom scatterin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 75 publications
4
43
0
Order By: Relevance
“…This indicates that, in contrast to the former calculations, a systematic treatment of electron–atom collisions is essential. For a detailed treatment of electron–atom collisions, see also Rosmej et al and Adams et al We conclude that the use of the dynamic potential leads to a good agreement with results obtained from the simulations performed in Norman and Saitov …”
Section: Results For Reflectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that, in contrast to the former calculations, a systematic treatment of electron–atom collisions is essential. For a detailed treatment of electron–atom collisions, see also Rosmej et al and Adams et al We conclude that the use of the dynamic potential leads to a good agreement with results obtained from the simulations performed in Norman and Saitov …”
Section: Results For Reflectivitymentioning
confidence: 99%
“…A more general form for the collision frequency is given by ν ( ω ) = r ( n , T , ω ) ν ( ω ) (1) , where the expression for r ( n , T , ω ) is given in terms of equilibrium correlation functions. For fully ionized plasmas in the static limit, ω → 0, the renormalization function interpolates between the low‐density Spitzer limit and the high‐degeneracy Ziman limit , . The renormalization function depends on the frequency ω and approaches the high‐frequency limit 1, limωr(),,nTω=1.…”
Section: Dynamic Collision Frequencymentioning
confidence: 99%
“…The screened HF interaction potential is repulsive at large distances. This repulsion is a result of the plasma polarization around the atom , . Considering the screened HF interaction potential, from Figure a we see that, in comparison with the case of λ = 0, the quantum non‐locality ( λ ≠ 0) leads to a stronger repulsion at large distances and to the stronger attraction at close inter‐particle distances.…”
Section: E–h Scattering In a Dense Plasmamentioning
confidence: 92%
“…In Figure a, the transport cross‐sections calculated using the screened optical potential (sum of potentials and ) and the optical potential for the isolated atom–electron interaction are compared with the experimental data by Crompton et al and Register et al Additionally, in Figure the results of Rosmej et al and Adibzadeh and Theodosiou are shown. The calculations of Adibzadeh and Theodosiou are for the isolated atom–electron scattering, and the result of Rosmej et al was obtained on the basis of the optical potential taking into account the exchange potential and screening by a classical plasma.…”
Section: E–h Scattering In a Dense Plasmamentioning
confidence: 99%
See 1 more Smart Citation